#MeToo Movement: Global Civil Society in Fighting Sexual Harassment in South Korea - Yana Dwifa Saraswati; Najamuddin Khairur Rijal; Shannaz Mutiara Deniar (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study discusses the problem of sexual harassment that occurs in South Korea, where it is often discussed but the culture in South Korea is an obstacle to resolving or reducing the crime of sexual harassment. So in 2018 South Korea adopted a movement that fights for victims of sexual harassment, the #MeToo movement. The objective of study then discusses the role of the #MeToo movement in fighting for the rights of victims of sexual harassment. The concept used is the Global Civil Society, Patriarchy Culture and Sexual Harassment. The research method is qualitative-descriptive, with data collection through literature study such as journals, books, article and other literature. The data analysis involved four stages there are data collection, data reduction, data presentation and drawing conclusion. The results of the study found that the #MeToo movement helps or builds confidence and security for victims so that victims can report their sexual harassment acts, help victims to get legal justice, and then form solidarity between victims, the communities and the government to stand on the side of the victims.